PERBEDAAN EFEKTIFITAS GUIDED IMAGERY DAN KOMPRES HANGAT TERHADAP PENURUNANAN SKALA NYERI DISMINORE PADA SISWI SANTRI DIPONDOK PESANTREN AL BAROKAH KABUPATEN DHARMASRAYA - Astuti Ardi Putri, Candra Syah Putra (LPPM Universitas Muhammadiyah Sumatera Barat, 2016)
Disminore problem is severe pain before menstruation, forcing the patient to rest. The solution is used to reduce pain ie non-pharmacological therapy guided imagery and warm compresses. The method used in this study is Quasi Experiment with one group pretest-posttest study subjects are grouped into two groups of experimental and control groups. The research proves a pain scale of respondents before being given a guided imagery intervention majority (60%) had moderate pain, and after given a guided imagery intervention majority (66%) to mild pain. While the characteristic timescales decrease in pain after the intervention given average 17.27 minutes. In the group of warm compresses research proves of 15 respondents before it is given a warm compress large proportion (53.3%) experienced moderate pain after the intervention was given a warm compress to prove the majority (86.7%) to mild pain, by the time range after scaling back pain by intervening warm compresses average decreased for 4.60 minutes. warm compresses difference test results are more effective against pain reduction reaction disminore compared to guided imagery proved the difference in mean response time 12.67 minutes. Keywords: Guided Imagery, Warm Compress and Disminore